Uncertainty shocks and asymmetric dynamics in Korea: a non-linear approach. Issue 6 (1st February 2019) - Larcher, Kevin; Kim, Jaebeom; Kim, Youngju
ABSTRACT: This study investigates the impact of uncertainty shocks on macroeconomic activity in Korea. For this purpose, a Smooth Transition VAR model is employed to document the state-dependent dynamics of two distinct types of uncertainty shocks, namely, financial market based and news-based. When non-linearity is allowed to play a role in our model, quantitatively very different asymmetric dynamics are observed. Following inflation targeting, the responses tend to be smoother and less pronounced. Our empirical results support the view that the link between uncertainty and macroeconomic activity is clear over both recessions and expansions. Furthermore, the impact of uncertainty shocks is more pronounced when economic activity is depressed especially after shocks originate from the financial market, and not from news-based policy uncertainty in Korea.